Second law analysis of small scale organic rankine cycle - Pathak S.; Jha A.; Shukla S.K. (My University, 2025)
This paper essentially consists of energy and exergy analysis of a solar powered organic rankine cycle (ORC). R245fa has been used as the working fluid in this low-temperature organic rankine cycle for 1 kW power generation. The exergetic efficiency and exergy destruction rates are calculated for this system using second law analysis. The results show that the energetic efficiency reaches its peak value of 7.53% while exergetic efficiency is found to have a peak efficiency of 32.36% at the same inlet expander temperature. Also, the maximum exergy destruction occurs in the evaporator rather than in the condenser as evident by this analysis. It may be inferred that performance of any organic rankine cycle can be estimated by exergetic efficiency more precisely than energetic efficiency. The goal of this research is to highlight that this kind of system can be used for generating electrical power in buildings. © 2018-Kalpana Corporation.